2010
DOI: 10.1097/iae.0b013e3181bd2d7b
|View full text |Cite
|
Sign up to set email alerts
|

Histology of Fibrovascular Membranes of Proliferative Diabetic Retinopathy After Intravitreal Injection of Bevacizumab

Abstract: The vascular endothelial cells with decreased expression of vascular endothelial growth factor are still present in the fibrovascular membranes of patients with PDR after intravitreal injection of bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Accordingly, the F10 SLO may be useful in evaluating neovascular vessels in fibrovascular membrane in PDR and for determining the precise retinal changes in diabetic retinopathy. In previous reports, neovascular vessels without blood flow1,3 and apoptotic cells on the regressing vascular walls2 were observed histologically after IVB. In our study, staining of the neovascular tissue with hematoxylin-eosin disclosed that many neovascular capillaries were still present, but that only large vessels contained red blood cells (shown in Figure 2).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Accordingly, the F10 SLO may be useful in evaluating neovascular vessels in fibrovascular membrane in PDR and for determining the precise retinal changes in diabetic retinopathy. In previous reports, neovascular vessels without blood flow1,3 and apoptotic cells on the regressing vascular walls2 were observed histologically after IVB. In our study, staining of the neovascular tissue with hematoxylin-eosin disclosed that many neovascular capillaries were still present, but that only large vessels contained red blood cells (shown in Figure 2).…”
Section: Discussionmentioning
confidence: 83%
“…Recent reports have described the application of IVB in treating ocular neovascular disorders including PDR 810. IVB has also been reported to be effective in causing the regression of new vessels in PDR 13. Adjunctive use of intravitreal bevacizumab for severe PDR before vitrectomy significantly decreased bleeding from the vessels of the fibrovascular membrane during the vitrectomy 6,7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kubota et al reported that vascular endothelial cells lining along the fibrovascular membrane of proliferative diabetic retinopathy expressed VEGF, but the density of VEGF-positive cells decreased after intravitreal injection of bevacizumab. [44] Qian et al reported that vitreous concentrations of VEGF decreased after intravitreal injection of bevacizumab in eyes with proliferative diabetic retinopathy. [42] The differences between the reported studies and ours could be explained by the strength and duration of NV induction.…”
Section: Discussionmentioning
confidence: 99%
“…[22] In spite of abundant studies demonstrating the inhibition of NV formation on cornea and other tissues, the effects of bevacizumab on the expression of VEGF and its receptors in the cornea have seldom been reported. [42][44] …”
Section: Introductionmentioning
confidence: 99%